THE IMPACT OF PRICE AND SERVICE QUALITY ON CUSTOMER SATISFACTION THROUGH BRAND TRUST AT CAFE AOLA LAMONGAN - Sri Lestari, Damajanti; Utami Ady, Sri (Penerbit Lafadz Jaya, 2025)
Cafe Aola Lamongan, a renowned gastronomic establishment located in the Paciran coastal region, encounters difficulties in sustaining alignment between pricing, service delivery standards, and brand credibility, particularly during peak operating periods that result in patron dissatisfaction regarding delayed service and perceptions of inadequate value proposition. This investigation seeks to analyze the influence of pricing and service delivery on customer satisfaction through the intermediary function of brand trust at Cafe Aola Lamongan. The research employs a quantitative methodology utilizing survey instruments administered to 150 participants, chosen via purposive sampling techniques. Data examination was conducted using Smart PLS software to assess instrument validity and reliability, while evaluating structural connections among variables through path coefficient analysis, t-statistics, and p-value computations. The findings demonstrate that service delivery represents the predominant determinant affecting customer satisfaction, exhibiting a path coefficient of 0.647 and F-Square value of 0.484, whereas pricing constitutes the principal element for establishing brand trust with a coefficient of 0.630 and F-Square value of 0.552. Brand trust substantially mediates the connection between pricing and customer satisfaction with a coefficient of 0.165, and between service delivery and customer satisfaction with a coefficient of 0.087. The study suggests that Cafe Aola Lamongan should emphasize enhancing service delivery through continuous employee development programs, uphold stable pricing approaches to reinforce brand trust, and establish more effective customer flow management systems to guarantee continued patron satisfaction.